2014
DOI: 10.1007/s00429-014-0957-8
|View full text |Cite
|
Sign up to set email alerts
|

Rapid treatment-induced brain changes in pediatric CRPS

Abstract: To date, brain structure and function changes in children with complex regional pain syndrome (CRPS) as a result of disease and treatment remain unknown. Here, we investigated (a) gray matter (GM) differences between patients with CRPS and healthy controls and (b) GM and functional connectivity (FC) changes in patients following intensive interdisciplinary psychophysical pain treatment. Twenty-three patients (13 females, 9 males; average age ± SD = 13.3 ± 2.5 years) and 21 healthy sex-and age-matched controls … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
102
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(107 citation statements)
references
References 154 publications
(190 reference statements)
2
102
3
Order By: Relevance
“…One study that contrasted brain resting cerebral blood flow between two chronic orofacial pain disorders, temporomandibular disorders and trigeminal neuropathic pain, found that both patient groups had increased DLPFC resting cerebral blood flow compared to pain-free controls, suggesting that spontaneous pain is related to DLPFC activity 111 . Other studies have reported lower gray matter volume (GMV) or thinner cortices in the DLPFC in patients with chronic pain, including irritable bowel syndrome 9, 90 , chronic low back pain 3, 85, 92, 110 , migraine 38 , trigeminal neuralgia 35, 66 , chronic post-traumatic headache 65 , and complex regional pain syndrome 26 . In some cases, these structural abnormalities were correlated with pain catastrophizing or other clinical characteristics 38 .…”
Section: Abnormal Dlpfc Structure In Chronic Painmentioning
confidence: 99%
See 1 more Smart Citation
“…One study that contrasted brain resting cerebral blood flow between two chronic orofacial pain disorders, temporomandibular disorders and trigeminal neuropathic pain, found that both patient groups had increased DLPFC resting cerebral blood flow compared to pain-free controls, suggesting that spontaneous pain is related to DLPFC activity 111 . Other studies have reported lower gray matter volume (GMV) or thinner cortices in the DLPFC in patients with chronic pain, including irritable bowel syndrome 9, 90 , chronic low back pain 3, 85, 92, 110 , migraine 38 , trigeminal neuralgia 35, 66 , chronic post-traumatic headache 65 , and complex regional pain syndrome 26 . In some cases, these structural abnormalities were correlated with pain catastrophizing or other clinical characteristics 38 .…”
Section: Abnormal Dlpfc Structure In Chronic Painmentioning
confidence: 99%
“…Although the pattern of gray matter abnormalities is not necessarily consistent across all chronic pain disorders, there appears to be some level of convergence across different chronic pain disorders. For example, patients with chronic back pain 3, 79, 85, 92 , migraine 44, 77, 102 , trigeminal neuropathic pain 22 , hypnic headache 37 , chronic post-traumatic headache 65 , hip osteoarthritis 78, 79 , complex regional pain syndrome 26 have reduced dorsolateral prefrontal cortex (DLPFC) gray matter, compared to healthy subjects (for a comprehensive review, see 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…We assume that Sarah will display a heightened pain prediction [ p(pain) ]. These heightened pain predictions may have formed via associative learning processes (interoceptive fear conditioning; Bouton et al, 2001; Vlaeyen and Linton, 2012; Zaman et al, 2015), via biological processes such as structural brain changes due to ongoing pain experiences (Erpelding et al, 2014), via exposure to early infant pain experiences such as burn injuries or neonatal nociceptive input resulting in exaggerated expectations of pain in later life (Victoria and Murphy, 2015), or via social influences, e.g., anxious parental reactions to the child’s pain. Once Sarah has inferred and perceived pain, this heightened pain predictions might also emerge as a result of the perception itself as the posterior always becomes the prior for the next perceptual inference.…”
Section: Why Individuals With Chronic Pain Perceive Pain When Harmlesmentioning
confidence: 99%
“…For instance, after 3 to 4 weeks of pain rehabilitative treatment in pediatric complex regional pain syndrome, cortical thickness increased in regions implicated in pain modulation along with lower pain intensity. 26 In chronic low back pain, gray matter changed after microsurgical lumbar discectomy 46 in the basal ganglia and hippocampus; regions involved in motor, emotional, cognitive, and learning. 3,55 Reversal of cortical thinning abnormalities in the insula was reported posttreatment in low back pain patients that correlated with reduced pain.…”
Section: Discussionmentioning
confidence: 99%